"A terra natural desta nação guarani” : identidade, memória e reprodução social indígena no Vale do Jacuí (1750-1801) - Ribeiro, Max Roberto Pereira (Universidade do Vale do Rio dos Sinos, 2017)
The focus of this thesis is the building of the identity of a part of the Uruguay river missions’ population, having the period between the Madrid Treaty (1750) until the definitive annexation of the indigenous settlements by the Portuguese (1801), considering the political and social transformations that happened due to the colonial situation in which the Spanish and the Portuguese had involved indigenous in. This period is characterized as a conjuncture of territorial disputes between the Iberians and the Indians that manifested a specific type of social identity that was built from the territory because of those very disputes. Therefore, the thesis has the aim of understanding how this type of identity was built in a moment of transformation and how it was shaped throughout time by relationships with the Portuguese. It was opted for a methodology that is inspired by the microhistory, portraying an intensive analysis of a varied set of sources, such as reports, Portuguese government documents, ecclesiastical records – containing visits, ordinations and christening books – with the purpose of identifying and analyzing the clues of the process of identity building of those Guarani. The thesis presents three hypotheses concerning this process of identity building. The first contends that the conservation of the memories of ancestral experiences of life in the missions was used in the building, not only as narratives about the past, but also as a model of social organization. The second hypothesis defends the idea that his identity belonged to the remaining Tape groups. The third on upholds that the identity helped them to make themselves different from other social actors and that, through this very identity, they had an organizational unity that allowed the coexistence with other indigenous groups without having the need of becoming a part of them. The conclusion is that the amount of Guarani studied here did not insert themselves in a new society of settlers. The Indians had to deal with the systemic advance of the Portuguese finding ways of coexisting, especially after 1750. Even when facing that inevitable situation, their identity and uses of memory allowed the Indians to trigger some degree of malleability to face the hardship that were presented to them, thus making their organization system reproduce itself.
Keywords: Identidade; Memória; Indígenas; Reduções; Identity; Memory; Indians; Missions; ACCNPQ::Ciências Humanas::História